Examining the association of family environment and children emotional/behavioral difficulties in the relationship between parental anxiety and internet addiction in youth - Wang, Yuxin; Zhou, Keyin; Wang, Yang; Zhang, Jing; Xie, Yuanchen; Wang, Xin; Yang, Wenyi; Zhang, Xiyan; Yang, Jie; Wang, Fei (Frontiers in Psychiatry, 2024)
Associations between parental anxiety and adolescent internet addiction have been documented in the literature; however, few studies have analyzed the role of the family environment in this relationship. This study aims to explore the relationship between parental anxiety and adolescent internet addiction while also investigating the indirect relationships involving multiple dimensions of the family environment and child emotional behavior issues. We conducted surveys among 6,296 parent-child pairs in the sample. Correlation analysis revealed that the family environment and adolescent emotional behavior issues played an indirect relationship in the link between parental anxiety and internet addiction. The findings emphasize the importance of addressing parental anxiety and fostering a positive family environment as effective measures to alleviate adolescent emotional behavior problems and reduce the risk of internet addiction.